Lärt gräl: Fredmans Sång N:o 28 och 1700-talets disputationskultur - Burman, Lars (Tidskrift för litteraturvetenskap, 2014)
Academic Quarrels. Carl Michael Bellman’s Fredman’s Song 28 and the 18th Century Disputations In Carl Michael Bellman’s (1740–1795) song, ”Fredmans Sång 28” (c. 1780), the fictional drinking hero Movitz has left Stockholm for studies at Uppsala University. He soon returns to Stockholm, where a disputation is staged in a tavern, a disputation which soon turns into a bacchanalian chaos. This article analyses song 28 and how it relates to 18th century academic disputations. It explores how Bellman’s parody technique draws on these austere ceremonies, which would have been well-known among his audience. The parody is emphasized through the use of the melody from the famous student-song ”Ecce quam bonum”. Bellman himself studied in Uppsala for a short period in 1758, and it is made clear that he ought to have been present at disputations, at least at his own student organization ”Stockholms Nation”.